USER INTERFACE DESIGN AND INFORMATION SYSTEMS USAGE: A CASE STUDY OF TVET INFORMATION SYSTEM AT IPRC KIGALI - David, MugumeNkuranga; Ongus, Raymond; Gitonga, Mbaabu; Alfred, MukuruSsessaazi (International Journal of Engineering Technologies and Management Research, 2018)
The purpose of this study was to assess the effect of User Interface Design on Information Systems Usage for the Technical Vocational and Educational Training Information System at (TVET-IS) at Integrated Polytechnic and Regional Centre (IPRC) Kigali, with the following objectives; to examine the design of the user interface of TVET information systems at IPRC Kigali; to evaluate the level of usage of the TVET information system at IPRC Kigali; and to establish the relationship between TVET Information system user interface design and its usage. The study was a descriptive research design with a simple random sampling method used to select academic, administrative, and ICT staff respondents for administration of the questionnaire. From a target population of 308, a sample size of 174 staff was selected. Data was analyzed using SPSS version 22 with tables, frequencies and charts used for presentation. TVET IS components considered in this research, were interface usability, interface layout and the interface design technology. The correlation coefficient (r = 0.587, P<0.01) was found between interface layout and IS Usage implying that the relationship was positive and statistically significant. Similarly r = 0.743, P<0.01 for the relationship between interface design Technology and IS Usage implying that the relationship was positive and statistically significant. Correlation coefficient (r = 0.642) and p-value (0.000) was produced between interface usability and IS usage meaning the relationship was positive and statistically significant. The TVET IS was used for data entry, retrieval and data security to a very minimal degree. The finding therefore showed that the relationship between User Interface Design and IS usage with multiple correlation coefficient R = 0.994, provided evidence that user interface design and TVET IS usage was positive and statistically significant. The recommendation after this study and findings is that IPRC Kigali administration should set up policies and mechanism to have all its activities done online with much emphasis on TVET Information System since most modules for the activities are included in this system. The online activities would include those activities that bring incentives to the staff and activities like accreditation of programs and accreditation of schools be done online through TVET-IS. More coaching is paramount to the users of the system so that they are very conversant with the system and technologies used. Workforce Development Authority should only accept online applications for accreditation and its approval to IPRC through TVET Information. The government should set the policy where online services are paramount and this would encourage institutions like IPRC Kigali to use the available systems like TVET-IS to the maximum.